Designing online learning with Flash - Moore, David Richard 1969- (Pfeiffer essential resources for training and HR professionals, 2009)
"There is a need for a book that provides a model of learning that is appropriate for online learning as well as teaches the user how to create potent Flash applications to deliver online learning content. This book is an Adobe Flash tutorial set in an instructional design context. It demonstrates how to develop Flash tutorials for teaching facts, concepts, principles, and procedures using Merrill s Component Display Theory. All the book s source files are provided as well as Adobe Captivate tutorials demonstrating the procedures"--Resource description page